Relationship between Self- Efficacy and Push – Ups Performance after Seven Days of Free Trial Gym Sessions - Ismail, Mazlan (International Journal of Psychosocial Rehabilitation, 2020)
The present study examines the relationship between self-efficacy of gym members and push – ups test. The data was collected from 34 female participants age ranged 19 - 39 years old (M =30.29, SD=32.00). The participants are 7 days (trial pass) gym visitors who came to the gym every day without any attachment with instructors. Push – ups selfefficacy scale was adapted from the previous scale particularly to measure push – ups performance of the members. Pearson correlation showed no relationship between self – efficacy of the female gym members and push – ups scores. Findings in this study demonstrate that self – efficacy scale specifically in exercise tasks is also a good instrument to assess the performance of exercise program. However, the push – ups test may not consider as an instrument to assess exercise performance for participants who just involved (7 days) in exercise session. Future research may focus on the members’ motivation level prior to exercise or gym session.